Partial mitochondrial involvement in the antiproliferative and immunostimulatory effects of PT-112 - Ruth Soler-Agesta; Manuel Beltrán-Visiedo; Ai Sato; Takahiro Yamazaki; Emma Guilbaud; Christina Y. Yim; Maria T. Congenie; Tyler D. Ames; Alberto Anel; Lorenzo Galluzzi (OncoImmunology)
PT-112 is a novel small molecule exhibiting promising clinical activity in patients with solid tumors. PT-112 kills malignant cells by inhibiting ribosome biogenesis while promoting the emission of immunostimulatory signals. Accordingly, PT-112 is an authentic immunogenic cell death (ICD) inducer and synergizes with immune checkpoint inhibitors in preclinical models of mammary and colorectal carcinoma. Moreover, PT-112 monotherapy has led to durable clinical responses, some of which persisting after treatment discontinuation. Mitochondrial outer membrane permeabilization (MOMP) regulates the cytotoxicity and immunogenicity of various anticancer agents. Here, we harnessed mouse mammary carcinoma TS/A cells to test whether genetic alterations affecting MOMP influence PT-112 activity. As previously demonstrated, PT-112 elicited robust antiproliferative and cytotoxic effects against TS/A cells, which were preceded by the ICD-associated exposure of calreticulin (CALR) on the cell surface, and accompanied by the release of HMGB1 in the culture supernatant. TS/A cells responding to PT-112 also exhibited eIF2α phosphorylation and cytosolic mtDNA accumulation, secreted type I IFN, and exposed MHC Class I molecules as well as the co-inhibitory ligand PD-L1 on their surface. Acute cytotoxicity and HMGB1 release caused by PT-112 in TS/A cells were influenced by MOMP competence. Conversely, PT-112 retained antiproliferative effects and its capacity to drive type I IFN secretion as well as CALR, MHC Class I and PD-L1 exposure on the cell surface irrespective of MOMP defects. These data indicate a partial involvement of MOMP in the mechanisms of action of PT-112, suggesting that PT-112 is active across various tumor types, including malignancies with MOMP defects.